Challenges in supporting the principles of the anti-asylum fight - Lira, Gabriela Fernandes Chaves; Oliveira, Andreia (Argumentum, 2023)
This article is a study on the field of mental health and the re-asylum movement in Brazil. Bibliographical research and documentary analysis was conducted to identify areas of tension and dispute in the country’s mental health policies for the period 2016-2022. Results identify a situation in which public policies are linked to Brazilian Psychiatric Reform. There are, however, re-asylum measures, defended by the private sector, with the expansion of psychiatric counter-reform and mental health proposals aimed at the interests of the private and philanthropic sectors. This demands the strengthening of Brazilian Psychiatric Reform and the Anti-Asylum Fight, aligned with the social struggles of workers and a democratic and free society.